BindingDB Entry 50001004: Metallo-β-lactamase inhibitors by bioisosteric replacement: Preparation, activity and binding. - BindingDB (BindingDB, 2020)
Small molecule binding data for protein GIM-1 and VIM-2, Uniprot Q704V1 and Q9K2N0